Provenance analysis of the Rhenohercynian Basin and its southern collision zone: transition from a Silurian volcanic arc to the Rhenohercynian shelf (Central European Variscides) - Wolfgang Dörr; Joachim Blau; Linda Marko; Petra Petschick; Rainer Petschick; Peter Prinz-Grimm; Janina Schastok; Felicitász Velledits (International Journal of Earth Sciences, 2025)

Clay mineral formation in Permian rocks of a geothermal borehole at Northern Upper Rhine Graben, Germany - Lan Nguyen-Thanh; Rafael Ferreiro Mählmann; Thao Hoang-Minh; Rainer Petschick; Thomas Reischmann; Heinz-Dieter Nesbor; Myriam Ruttmann; Johann-Gerhard Fritsche (International Journal of Earth Sciences, 2021)
Hydrothermally altered rhyolite rocks in the Permian Donnersberg Formation of a geothermal borehole in the Northern Upper Rhine Graben (Germany) were investigated to find out answers for the low hydraulic conductivity of the rocks. The composition of clay minerals and the temperature of smectite–illite transformation were carried out using X-ray diffraction, X-ray fluorescence, transmission electron microscopy, Fourier transform infrared spectroscopy, and polarized-light microscopy analyses. Clay mineral (CM) composition includes illite/muscovite (1 M and 2 M 1 polytypes), illite–smectite interstratifications (IS-ml), smectite, and chlorite; and non-clay minerals such as quartz, feldspars, epidote, calcite, dolomite, and hematite were detected. The 2 M 1 -polytype mica might be the only primary sheet silicates from the parent rocks, while the others occur as authigenic neo-formed CMs under heat flow and geothermal gradient. The development of CMs indicates different mechanisms of illitization and smectitization. Based on the texture, morphology, structure/polytype, and chemistry of rocks and minerals, in particular CMs, the study grouped the CM formation into three transformation processes: smectitization during magma cooling and possible contact metamorphisms with decreasing and low temperature, smectite illitization controlled by burial diagenesis and hydrothermal alteration, and illite smectitization followed exhumation and Cenozoic subsidence with decreasing temperature. The rhyolites were altered to all of the orders IS-R0, IS-R1, and IS-R3 by the dissolution-precipitation and layer-to-layer mechanisms. The first one supported small xenomorphic plates and flakes of 1 M d , elongated particles of 1 M , and pseudo-hexagonal forms of 2 M 1 . The second one could lead to the platy particles of 1 M d and 2 M 1 polytypes. The dominant temperature range for the transformation in the area has been 140–170 °C– ~ 230 °C.

New structural and U–Pb zircon data from Anafi crystalline basement (Cyclades, Greece): constraints on the evolution of a Late Cretaceous magmatic arc in the Internal Hellenides - Silviu O. Martha; Wolfgang Dörr; Axel Gerdes; Rainer Petschick; Janina Schastok; Paraskevas Xypolias; Gernold Zulauf (International Journal of Earth Sciences, 2016)

Upper crustal emplacement and deformation of granitoids inside the Uppermost Unit of the Cretan nappe stack: constraints from U–Pb zircon dating, microfabrics and paleostress analyses - Tilo Kneuker; Wolfgang Dörr; Rainer Petschick; Gernold Zulauf (International Journal of Earth Sciences, 2015)